Brain abnormalities in Sjogren syndrome with recurrent CNS manifestations: association with neuromyelitis optica. - Min, J; Kim, H; Kim, B; Lee, K; Sunwoo, I; Kim, S; Kim, B; Kim, S; Park, MS; Waters, P; Vincent, A; Sung, J; et al. (2009)
BACKGROUND AND OBJECTIVES: Optic neuritis or longitudinally extensive myelitis in Sjogren syndrome (SS) suggests a neuromyelitis optica spectrum disorder (NMOSD). However, brain abnormalities of SS remain to be elucidated for the association with neuromyelitis optica (NMO). METHODS: Twelve primary SS patients (all women, 42 +/- 13.2 years) who had recurrent central nervous system (CNS) manifestations with brain involvement were retrospectively identified. Brain MRI, and neurologic and serologic findings were analyzed with the measurement of anti-aquaporin-4 antibody (AQP4-Ab). RESULTS: All patients showed brain lesions characteristic of NMO as follows: 1) the involved sites adjacent to the third and fourth ventricles and in the posterior limb of the internal capsule, 2) unique configurations, such as the longitudinal course from the internal capsule to the midbrain, large cerebral or cerebellar lesions over 3 cm, and cavity-like formations. AQP4-Ab was positive in six of eight patients tested, and all the seropositive patients showed lesions with increased diffusion, suggestive of vasogenic edema. Four patients met the revised criteria of NMO, and nine had features of NMOSDs. Of the remaining three patients showing only brain involvement, one had AQP4-Ab. CONCLUSIONS: This study demonstrates that SS patients with recurrent CNS involvement have brain abnormalities characteristic of NMO and AQP4-Ab in Korea. The presence of AQP4-Ab in one SS patient with only brain involvement may suggest that the coexistence of NMO should be explored in SS patients with recurrent CNS manifestations, even without optic neuritis or myelitis.